The impact of the virtual classroom on the development of oral communicative competence in qualifying secondary school learners: A case study of the provincial direction of national education in Agadir - AJDI, Nihal; BOURRAY, Mounir; TCHAMEKH, Zineb (Edelweiss Applied Science and Technology, 2024)
The period, mandated by health decision-makers in Morocco, was characterised by a certain improvisation in terms of the approaches used to enssure some form of pedagogical continuity. WhatsApp groups emerged as one of the methods adopted in an imposed manner by most teachers who were content with the digital tools available. In this context, our article aims to analyze the technical, didactic and pedagogical functioning of distance sessions programmed in synchronous mode, in order to determine whether virtual classes simulated real ones. It also seeks to study their effect on the development of oral communicative competence in Moroccan high school students. For this, we employed a mixed methodology: online questionnaire and semi-directive online interview process. The results indicated that no oral production was carried out, and hence there is a barrier to achieve an effective level of communicative competence during virtual sessions.